PENGARUH LATIHAN PIRAMID SET DAN SUPER SET PADA STATUS BODY MASS INDEKS TERHADAP PENURUNAN LEMAK DAN PENAMBAHAN MASSA OTOT - jonathan samsi, joe black (2020)
ABSTRACT THE INFLUENCE OF PYRAMID SET AND SUPER SET TRAINING MODELS IN BODY MASS INDES (BMI) STATUS ON THE REDUCTION OF BODY FAT AND ADDITION OF MUSCLE MASS The purpose of this study was to determine the differences in the effect of the exercise model that is Piramid set T and Super Set on members who have ideal and not ideal BMI levels on Body Fat and hipertrofi muchel. Experimental method with 2x2 factorial design. The sample of this research is 20 people, 10 men and 8 women. The sampling technique uses a random assignment sampling technique on UKM IBAFF UPI members in Bandung. Data collection in this study used Karada Scan Body Composition. Data analysis using SPSS version 21 with hypothesis testing through Two Way Anova. The results of the analysis and calculation of the data revealed that the weight training exercise model affected the reduction in fat loss body, the interaction between the training model and BMI ideal and BMI not Ideal of the exercise towards the reduction in body fat, the Super set model was better used than the piramid set training model in the BMI Ideal group for the reduction body fat and both weight training models have a similar or equal effect on decreasing body fat in the BMI not ideal group. The conclusion of this study is that the pyramid set model is better used for the BMI ideal group, whereas for the BMI not ideal group can use both of these exercise models to reduce body fat percentage. key words: Weight Training Exercise Model, Piramid set, Super Set, Body Fat, mass Muscel, Body Mass Index.